2015
DOI: 10.1515/ejnm-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: potential model for complement-stealth delivery systems

Abstract: Abstract:Exosomes are nature's nanocarriers that transport biological information in humans. Their structural properties, origin and functions are making them interesting objects for the diagnosis of diseases, such as cancer, and also, as innovative tools for drug delivery. The interaction of exosomes with the immune system has been one of the focal points of interest; nevertheless their "stealth" properties helping to avoid adverse immune reactions are still not fully understood. In this review, after giving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…In contrast to liposomes, EVs have conserved membranous structures, including natural corona, lipid composition, (trans-) membrane proteins, receptors as well as uptake and fusion modalities, which are comparable to those in cells ( 165 ). Thus, EVs seem to overcome the CARPA limitations caused by liposomes or nanoparticle-based delivery systems and represent highly promising therapeutic carriers ( 167 ).…”
Section: Clinical Relevancementioning
confidence: 99%
“…In contrast to liposomes, EVs have conserved membranous structures, including natural corona, lipid composition, (trans-) membrane proteins, receptors as well as uptake and fusion modalities, which are comparable to those in cells ( 165 ). Thus, EVs seem to overcome the CARPA limitations caused by liposomes or nanoparticle-based delivery systems and represent highly promising therapeutic carriers ( 167 ).…”
Section: Clinical Relevancementioning
confidence: 99%
“…At the same time this provides an opportunity for investigating the application of EVs as DDS, but potentially without CARPA triggering. EVs may have the potential to overcome CARPA effects as some studies claimed that EVs consist of a natural cocktail of biomolecules that do not cause adverse reactions linked to liposomal particle infusion [270,271]. But still, regarding possible CARPA adverse reactions after administration of EVs, their occurrence remains uncertain.…”
Section: Complement Activation-related Pseudoallergy (Carpa) Upon Nan...mentioning
confidence: 99%
“…However, in some studies using pig models, CARPA-related adverse effects were not observed after intracardiac administration of human MSC-derived EVs, while low doses of liposomes could induce shock-like symptoms [46,47]. Regarding the CARPA adverse reactions after administration of EVs, these remain uncertain and demand extensive research as the current experimental evidence is too limited [46,47,270,273]. Of note, it is generally accepted that the choice of species for preclinical validation is important to assess possible adverse reactions after infusion of EVs and liposomes [3].…”
Section: Complement Activation-related Pseudoallergy (Carpa) Upon Nan...mentioning
confidence: 99%
“…Other demonstrated potential exosome surface activators of targeted cells include: antibody (Ab) free light chains [ 61 , 62 , 63 , 64 ]; αβ -T cell Ag/MHC receptors [ 65 , 66 ]; procoagulants [ 67 , 68 ]; tetraspanins [ 69 , 70 ]; TIM4-binding phosphatidyl serine [ 71 ]; heparin-binding proteins [ 72 ]; histones; and annexins [ 73 , 74 ]; MHC class I and II; immune checkpoint or negative co-stimulation molecules (PD1, PDL-1) [ 75 , 76 ]; complement components [ 77 , 78 ]; glycosaminoglycans and proteoglycans [ 79 ]; binders of the TAM family of tyrosine kinases [ 80 ]; enzymes like ADAM family members [ 81 ]; sialidases [ 82 , 83 , 84 ]; DNA [ 85 , 86 , 87 ]; various lipoproteins like Apo E [ 78 ]; LDL receptor [ 88 ]; tumor necrosis factor receptor-1 [ 89 , 90 ] and various thiols.…”
Section: Exosome Surface Activation Of Target Cells Are Carrier Effectsmentioning
confidence: 99%